Vulnerable: The Law, Policy and Ethics of COVID-19 - Flood, Colleen; MacDonnell, Vanessa; Philpott, Jane; Thériault, Sophie; Venkatapuram, Sridhar (2020)
Vulnerable: The Law, Policy and Ethics of COVID-19 confronts the vulnerabilities that have been revealed by the pandemic and its consequences. It examines vulnerabilities for people who have been harmed or will be harmed by the virus directly and those harmed by measures taken to slow its relentless march; vulnerabilities exposed in our institutions, governance, and legal structures; and vulnerabilities in other countries and at the global level where persistent injustices affect us all. COVID-19 has forced us to not only reflect on how we govern and how we set policy priorities, but also to ensure that pandemic preparedness, precautions, and recovery include all individuals, not just some. ● TABLE OF CONTENTS ● INTRODUCTION : Overview of COVID-19: Old and New Vulnerabilities - Colleen M. Flood, Vanessa MacDonnell, Jane Philpott, Sophie Thériault and Sridhar Venkatapuram ●● SECTION A: WHO DOES WHAT? CHALLENGES AND DEMANDS OF CANADIAN FEDERALISM ● CHAPTER A-1: Have the Post-SARS Reforms Prepared Us for COVID-19? Mapping the Institutional Landscape - Katherine Fierlbeck and Lorian Hardcastle ● CHAPTER A-2: COVID-19 and First Nations’ Responses - Aimée Craft, Deborah McGregor, and Jeffery Hewitt ● CHAPITRE A-3 : Réflexions sur la mise en œuvre de la Loi sur la santé publique au Québec dans le contexte de la pandémie de COVID-19 - Michelle Giroux ● CHAPITRE A-4 : La COVID-19 au Canada : le fédéralisme coopératif à pied d’œuvre - David Robitaille ● CHAPTER A-5: Pandemic Data Sharing: How the Canadian Constitution Has Turned into a Suicide Pact - Amir Attaran and Adam R. Houston ● CHAPTER A-6: The Federal Emergencies Act: A Hollow Promise in the Face of COVID-19? - Colleen M. Flood and Bryan Thomas ● CHAPTER A-7: Resisting the Siren’s Call: Emergency Powers, Federalism, and Public Policy - Carissima Mathen ● CHAPTER A-8: Municipal Power and Democratic Legitimacy in the Time of COVID-19 - Alexandra Flynn ●● SECTION B: MAKING SURE SOMEONE IS ACCOUNTABLE: PUBLIC AND PRIVATE RESPONSIBILITIES ● CHAPTER B-1: Ensuring Executive and Legislative Accountability in a Pandemic -Vanessa MacDonnell ● CHAPTER B-2: Good Governance: Institutions, Processes, and People - Mel Cappe ● CHAPTER B-3: The Duty to Govern and the Rule of Law in an Emergency - Grégoire Webber ● CHAPTER B-4: Does Debunking Work? Correcting COVID-19 Misinformation on Social Media - Timothy Caulfield ● CHAPTER B-5: The Media Paradox and the COVID-19 Pandemic - Jeffrey Simpson ● CHAPTER B-6: Governmental Power and COVID-19: The Limits of Judicial Review - Paul Daly ● CHAPTER B-7: Liability of the Crown in Times of Pandemic - Marie-France Fortin ● CHAPTER B-8: Balancing Risk and Reward in the Time of COVID-19: Bridging the Gap Between Public Interest and the “Best Interests of the Corporation” - Jennifer A. Quaid ●● SECTION C: CIVIL LIBERTIES VS. IDEAS OF PUBLIC HEALTH ● CHAPTER C-1: Civil Liberties vs. Public Health - Colleen M. Flood, Bryan Thomas, and Dr. Kumanan Wilson ● CHAPTER C-2: Privacy, Ethics, and Contact-Tracing Apps - Teresa Scassa, Jason Millar, and Kelly Bronson ● CHAPTER C-3: Should Immunity Licences be an Ingredient in our Policy Response to COVID-19? - Daniel Weinstock and Vardit Ravitsky ● CHAPTER C-4: The Punitive Impact of Physical Distancing Laws on Homeless People - Terry Skolnik ● CHAPTER C-5: The Right of Citizens Abroad to Return During a Pandemic - Yves Le Bouthillier and Delphine Nakache ●● SECTION D: EQUITY AND COVID-19 ● CHAPTER D-1: How Should We Allocate Health and Social Resources During a Pandemic? - Sridhar Venkatapuram ● CHAPITRE D-2 : COVID-19 et âgisme : crise annoncée dans les centres de soins de longue durée et réponse improvisée ? - Martine Lagacé, Linda Garcia et Louise Bélanger-Hardy ● CHAPTER D-3: Fault Lines: COVID-19, the Charter, and Long-term Care - Martha Jackman ● CHAPTER D-4: The Front line Defence: Housing and Human Rights in the Time of COVID-19 - Leilani Farha and Kaitlin Schwan ● CHAPTER D-5: COVID-19 in Canadian Prisons: Policies, Practices and Concerns - Adelina Iftene ● CHAPTER D-6: Systemic Discrimination in Government Services and Programs and Its Impact on First Nations Peoples During the COVID-19 Pandemic - Anne Levesque and Sophie Thériault ● CHAPTER D-7: Preventing the Spread of Anti-Asian Racism: Including Critical Race Analysis in a Pandemic Plan - Jamie Chai Yun Liew ● CHAPTER D-8: Migrant Health in a Time of Pandemic: Fallacies of Us-Versus-Them - Y.Y. Brandon Chen ● CHAPTER D-9: Not All in This Together: Disability Rights and COVID-19 - Tess Sheldon and Ravi Malhotra ● CHAPTER D-10: Weighing Public Health and Mental Health Responses to Non-Compliance with Public Health Directives in the Context of Mental Illness - Jennifer A. Chandler, Yasmin Khaliq, Mona Gupta, Kwame McKenzie, Simon Hatcher, and Olivia Lee ●● SECTION E: THIS JOB IS GONNA KILL ME: WORKING AND COVID-19 ● CHAPTER E-1: Privatization and COVID-19: A Deadly Combination for Nursing Homes - Pat Armstrong, Hugh Armstrong, and Ivy Bourgeault ● CHAPTER E-2: A View from the Front Lines of a COVID-19 Outbreak - Jane Philpott ● CHAPTER E-3: Occupational Health and Safety and COVID-19: Whose Rights Come First in a Pandemic? - Katherine Lippel ● CHAPTER E-4: Risking It All: Providing Patient Care and Whistleblowing During a Pandemic - Vanessa Gruben and Louise Bélanger-Hardy ● CHAPTER E-5: Worked to the Bone: COVID-19, the Agrifood Labour Force, and the Need for More Compassionate Post-Pandemic Food Systems - Sarah Berger Richardson ●● SECTION F: GLOBAL HEALTH AND GOVERNANCE ● CHAPTER F-1: “Flattening the Curve” Through COVID-19 Contagion Containment - Anis Chowdhury and Jomo Kwame Sundaram ● CHAPTER F-2: The Plausibility and Resolvability of Legal Claims Against China and WHO under the International Health Regulations (2005) - Sam Halabi and Kumanan Wilson ● CHAPTER F-3: COVID-19 and Africa: Does “One Size Fit All” in Public Health Intervention? - Chidi Oguamanam ● CHAPTER F-4: Border Closures: A Pandemic of Symbolic Acts in the Time of COVID-19 - Steven J. Hoffman and Patrick Fafard ● CHAPTER F-5: COVID-19 and Accountable Artificial Intelligence in a Global Context - Céline Castets-Renard and Eleonore Fournier-Tombs ● CHAPTER F-6: International Trade, Intellectual Property, and Innovation Policy: Lessons from a Pandemic - Jeremy de Beer and E. Richard Gold ● CHAPTER F-7: COVID-19 Vaccines as Global Public Goods - Jason W. Nickerson and Matthew Herder https://press.uottawa.ca/vulnerable.html